Comparative evaluation of different cost effective ovulation induction drugs and their effect on follicular growth, endometrial thickness and pregnancy outcome - Narayanan, Madhumithaa; Jahaan, Uruj; Gupta, Neena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Ovulatory dysfunction is a common cause of female infertility, occurring in up to 20 - 30% of infertile women. The most commonly prescribed ovulation drugs are clomiphene citrate (CC), tamoxifen, aromatase inhibitors (such as letrozole) and gonadotropins. Objective of the study was to evaluate the efficacy of clomiphene citrate, letrozole and tamoxifen for ovulation induction in anovulatory infertility. Methods: Randomized open label interventional clinical trial. Patients were randomized to 3 drug groups. After baseline investigations, they were subjected to ovulation induction and then USG monitoring of follicular growth and ovulation. The primary outcome measured was occurrence of conception. Secondary outcome was effect on endometrial thickness and ovulation rate. Results: In the study, letrozole group showed 100% mono-follicular response. Mid cycle endometrial thickness in about 17% of cases in CC group is ≤8 mm. But all the cases in tamoxifen and letrozole group have ET >8 mm. This difference is statistically significant. The ovulation and conception rates are highest in letrozole group but the difference was not statistically significant. Conclusions: Letrozole produces higher mid cycle endometrial thickness, 100% mono follicular development than clomiphene and tamoxifen. This difference is found to be statistically significant. Ovulation rate and conception rate is highest in letrozole group. But there is no statistically significant difference among the three drugs.